Polarization-based puncturing pattern selection of shortened Polar code - Shunlan LIU; Aiming HU; Jianrong BAO (Dianxin kexue)
In order to solve the problem of inflexible Polar code length,a new puncturing pattern selection scheme based on feedback cost puncturing was proposed to generate shortened Polar codes.In this scheme,the Polarization effect was reserved,the sub-optimal subchannel was selected as the cost bit,the output bit corresponding to the cost bit was used as the puncturing pattern,and then the value of the cost bit is adjusted by feedback to obtain the shortened Polar code.Simulation results show that the performance of the proposed shortened Polar code is better than that of the shortened Polar code generated by bit-reversal permutation method,and the shortened Polar codes generated by direct puncturing method at the end under different channel and code rate conditions,and slightly weaker than that of the shortened Polar code proposed by Wang R and Liu R et al.In the AGWN channel,when the block error rate is 10-3,the proposed shortened Polar code with a code rate of 0.5 can obtain a gain of 0.5 dB compared with the shortened Polar code generated by bit-reversal permutation method,and the coding performance is greatly improved.